Measuring the level of empathic orientation in the student of the Faculty of Dentistry, University of Costa Rica - Howard Mora, Madeline (2014)
The learning of the dental career comprises the acquisition of knowledge of the basic and medical sciences, but generally, competences related to emotional intelligence are not encouraged. The objective of this research was to establish the level of empathic orientation of students from first to fifth year at the School of Dentistry of the University of Costa Rica according to gender and school year. Two hundred and ninety (69,7%) students completed the Jefferson Scale of Physician Empathy (JSPE). Two hundred and two were female and 88 (30,3%) were male. Our results are inconsistent with previous results reported in dental settings since students in fourth and fifth year showed higher empathy scores, and no difference was found related to gender.